IN SILICO STUDY: SECONDARY METABOLITES FROM JAMBOLAN (Syzygium Cumini L.) AS POTENTIAL BREAST CANCER TREATMENTS - Suherman, Meilia; Junaedi, Effan Cahyati; Prasetiawati, Riska; Purnamasari, Ade Rena (Faculty of Mathematic and Natural Science, Garut University, 2024)
Breast cancer ranks second in world cancer incidence rates in 2020, contributing to 2,261,419 new cases, or 11.7% of all new cancer cases globally. The search for cancer drugs that work selectively continues to be encouraged to obtain safe and effective therapy, particularly those derived from medicinal plants. Jambolan is a plant that can thrive in both subtropical and tropical climates, including Indonesia. Jambolan (Syzygium cumini L.) has 89% antioxidant activity and 69% cytotoxic activity against T47D cells. Pharmacophore modelling and molecular docking were used to study the binding of 117 active jambolan drugs to alpha and beta estrogen receptors. Rutin was found to be potentially selective for ER-Beta receptors, with a fit score of 53.13. Molecular docking to ER-Beta revealed that rutin has breast cancer activity with a free bond energy value of -10.5 kcal/mol and better conformation and affinity than native ligands (genistein). It also binds to essential amino acids as an anticancer breast at ARG 346 and GLU 305. Lipinski's rule of five prediction results and in silico ADMET prediction from rutin yielded results that met the candidate drug's parameters. Rutin is a potential therapeutic option for treating breast cancer by targeting the ER-Beta receptor.